2010
DOI: 10.1021/nn101735e
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation and Chemical Modification Using Microwave Irradiation Affording Highly Functionalized Graphene

Abstract: Efficient exfoliation of graphite flakes by sonicating them in benzylamine was accomplished, affording stable suspensions of few-layers graphene. The latter were chemically modified following the Bingel reaction conditions, with the aid of microwave irradiation, producing highly functionalized graphene-based hybrid materials. The resulting hybrid materials, possessing cyclopropanated malonate units covalently grafted onto the graphene skeleton, formed stable suspensions for several days in a variety of organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
104
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 77 publications
(120 reference statements)
4
104
0
Order By: Relevance
“…Further optimization of the solvents led to some improvements in the dispersibility of graphene. For instance, concentrations as high as 0.03 mg/mL, 0.1 mg/mL and 0.5 mg/mL were achieved using o-DCB [32] and perfluorinated aromatic solvents such as pentafluorobenzonitrile [33] and benzylamine [34], respectively. However, due to the long ultrasonication process, the lateral dimension of LPE graphene is relatively small (<3 m).…”
Section: Liquid-phase Exfoliation (Lpe)mentioning
confidence: 99%
“…Further optimization of the solvents led to some improvements in the dispersibility of graphene. For instance, concentrations as high as 0.03 mg/mL, 0.1 mg/mL and 0.5 mg/mL were achieved using o-DCB [32] and perfluorinated aromatic solvents such as pentafluorobenzonitrile [33] and benzylamine [34], respectively. However, due to the long ultrasonication process, the lateral dimension of LPE graphene is relatively small (<3 m).…”
Section: Liquid-phase Exfoliation (Lpe)mentioning
confidence: 99%
“…The resultant graphene still remains 4.2 wt.% as high temperature as 1000 8C. From the TGA curve, it can be concluded that the number of functional groups on the graphene sheets derivative from the stuff is less than that prepared using chemical methods [38,39]. Fig.…”
Section: Resultsmentioning
confidence: 89%
“…The first step (halogenation reaction), involving the intercalation of the halogen between the graphite layers, is accelerated by microwaves so that the modified material can then be easily exfoliated into monolayer graphene in organic solvents under mild sonication. Alternatively, stable suspensions of few-layer graphene have been obtained via the sonication of graphite flakes in benzylamine which were then subjected to cyclopropanation under MW irradiation [71]. If all-carbon graphene has so far attracted enormous attention in mass media, the fact that polymerized organic crystals can also be exfoliated to create two-dimensional sheets should likewise open a new age of innovation in materials design.…”
Section: Exfoliation Of Layered Materialsmentioning
confidence: 99%